Vocal tract characteristics in Parkinson's disease. Issue 3 (June 2016) - Gillivan-Murphy, Patricia; Carding, Paul; Miller, Nick
Abstract : Purpose of review: Voice tremor is strongly linked to the Parkinson's disease speech–voice symptom complex. Little is known about the underlying anatomic source(s) of voice tremor when it occurs. We review recent literature addressing this issue. Additionally we report findings from a study we conducted employing rating of vocal tract structures viewed using nasolaryngoscopy during vocal and nonspeech tasks. Recent findings: In Parkinson's disease, using laryngeal electromyography, tremor has not been identified in muscles in the vocal folds even when perceived auditorily. Preliminary findings using nasolaryngoscopy suggest that Parkinson's disease voice tremor is not associated with the vocal folds and may involve the palate, the global larynx, and the arytenoids. Tremor in the vertical larynx on /a/, and tremor in the arytenoid cartilages on /s/ differentiated patients with Parkinson's disease from neurologically healthy controls. Visual reliable detection of tremor when it is absent or borderline present, is challenging. Summary: Parkinson's disease voice tremor is likely to be related to oscillatory movement in structures across the vocal tract rather than just the vocal folds. To progress clinical practice, more refined tools for the visual rating of tremor would be beneficial. How far voice tremor represents a functionally significant factor for speakers would also add to the literature.